Analisis Strategi Pemasaran Syariah dalam Meningkatkan Penghasilan Coffee Shop Pada Era New-Normal di Kota Jambi (Studi Pada Coffee Shop Pedalaman) - M. Aditya; Saputra Siregar, Erwin; Syah Noor, Firman (Jurnal Pendidikan Tambusai, 2024)
This research aims to find out the sharia marketing strategy implemented by Coffee Shop Pedalaman in the New Normal era and the income of Coffee Shop Pedalaman. This research method is qualitative research and this research is a type of case study research. The informants of this research are the team leader, employees, and consumers of Coffee Shop Pedalaman. The techniques used when collecting data are utilizing observation, interviews and documentation studies. The technique in analyzing data presentation starts from collecting all data from observations, interviews and document studies. While in testing the validity of the data, namely by applying data triangulation. The results of the study show that it can be described that Coffee Shop Pedalaman in increasing income uses a 4p marketing mix strategy consisting of product, price, place, promotion. Without harming, cheating consumers or competitors. Based on the results found in this study, the researcher has suggestions that Coffee Shop Pedalaman in terms of the location used by Coffee Shop Pedalaman is very strategic, but it is a little narrow. Therefore, there should be additional petunuk about the location. Then expand marketing and promotional activities, participate in events to be better known by the wider community. As well as the importance of implementing a marketing strategy that must be maximized.